Motivational factors of management of intellectual work (Путеводитель предпринимателя)
The article explores the concepts of intellectual labour and the management of intellectual work. The six main motivational needs, lead, according to the author, employees of the management of intellectual work. Shows the methods of management of exposure to meet the motivational needs of employees, engaged in intellectual work.